Imagine this: Visualising a recent meal as bigger reduces subsequent snack intake. (1st February 2023) - Szypula, Joanna; Ahern, Amy; Cheke, Lucy
Abstract: Remembering a recent meal reduces subsequent intake of palatable snacks (i.e. the meal-recall effect), however, little is known about the factors which can potentiate this effect. The present experiment investigated whether a stronger meal-recall effect would be observed if recent consumption would be recalled in greater detail, than if it was recalled briefly. Moreover, it was investigated whether imagining a meal as bigger and more satiating than in reality could potentiate the meal-recall effect, and lead to lower intake. It was also explored whether mental visualisation tasks of a recent meal would affect the remembered portion size. Participants (N = 151) ate lunch at the laboratory, and then returned 3 h later to perform the imagination tasks and to participate in a bogus taste test (during which intake was covertly measured). Participants in the two main imagination task groups recalled the lunch meal and then either recalled the consumption episode in great detail or imagined the meal was larger and more filling than in reality. The results showed that imagining a recent meal as larger significantly reduced the quantity of biscuits eaten. However, contrary to the hypotheses, recalling a consumption episode in detail did not decrease snack intake. It was also shown that imagining a recent meal as larger than in reality did not lead participants to overestimate the true size of the meal. In fact, portion size estimations were significantly underestimated in that group. There were no significant estimation differences in any of the other groups. The results of this study suggest that the meal-recall effect can be an effective strategy to reduce food intake and may be amenable to strategic manipulation to enhance efficacy, but seems prone to disruption.